(untitled) (El-Wahat Journal for Research and Studies, 2026)
The present research is an investigatory paper headed to obtain comprehension about strategies in enhancing spelling skills used by Algerian students. The work deployed a mixed-method approach to gather data from the participants. A semi-structured questionnaire was conducted to 25 first year students at the department of English language, University of Ghardaia. The results of the investigation exhibited that the learners used strategies to enhance spelling accuracy, and more than half of them depend only on visual memory when checking the correct spelling. It is advocated that the foreign learners use several strategies and techniques that stemmed from diverse spelling teaching and learning approaches, namely: Targeted Practice, Mnemonic Devices, and Technology-Based Tools.